2013
DOI: 10.1016/j.ijpara.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the tissue factor pathway inhibitor-like Kunitz domain-containing protein family in Rhipicephalus microplus

Abstract: One of the principle mechanisms utilised by ticks to obtain a blood meal is the subversion of the host's haemostatic response. This is achieved through the secretion of saliva containing antihaemostatic proteins into the feeding lesion. Lineage-specific expansion of predicted secretory protein families have been observed in all previously studied ticks and occurred in response to adaptation to a blood-feeding environment. Of these, the predominant families are common between both hard and soft ticks. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 75 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Such protein families are found in the venoms of several other Metazoan species [2]. Examples of such venomous protein families found in tick saliva are defensins [65], lectins [66], cystatins [67], lipocalins [21,68-71], hyaluronidase [72], phospholipase A2 [73], Kunitz-like peptides [56,74,75], metalloproteases [76], AVIT [77], CAP proteins (Cysteine-Rich Secretion Proteins, Antigen 5, and Pathogenesis-Related) [2] and sphingomyelinase D [2]. …”
Section: Resultsmentioning
confidence: 99%
“…Such protein families are found in the venoms of several other Metazoan species [2]. Examples of such venomous protein families found in tick saliva are defensins [65], lectins [66], cystatins [67], lipocalins [21,68-71], hyaluronidase [72], phospholipase A2 [73], Kunitz-like peptides [56,74,75], metalloproteases [76], AVIT [77], CAP proteins (Cysteine-Rich Secretion Proteins, Antigen 5, and Pathogenesis-Related) [2] and sphingomyelinase D [2]. …”
Section: Resultsmentioning
confidence: 99%
“…With the exception of the annotated I. scapularis sialome [6,9], both protein BLAST [43] and PSI-BLAST [44] searches do not reveal any known or functionally described single Kunitz-domain peptide with the Cys motif of G3, G6 and G11. The proteins that slightly resemble the Cys motif of G6, and lack the archetypal Cys2 and Cys4 disulfide bridge, are the I. scapularis salivary Kunitz proteins Ixolaris [38] and Penthalaris [39], both possessing multiple Kunitz domains, and some members of the Kunitz family found in R. microplus [45]. An alignment using the classical Kunitz serine protease inhibitor BPTI (UniProt: P00974) with G1 and G7 shows the conserved positively charged arginine (Arg or R) or lysine (Lys or K), known as the P1 site that interacts with the negatively charged active site of serine proteases (highlighted blue in Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…This included studies of the BTSP family , the Kunitz/BPTI family (Dai et al 2012;Louw et al 2013;Mans and Neitz, 2004b;Mans et al , 2003b2002a;Schwarz et al 2014b), the lipocalin family (Beaufays et al 2008b;Mans, 2005;Mans and Neitz, 2004c;Ribeiro, 2008a, 2008b;Mans et al , 2008cMans et al , 2003a) and the apyrases (Stutzer et al 2009). These studies suggested that argasid BPTI anti-hemostatic factors share a common evolutionary pathway; that biogenic amine binding lipocalins and TXA 2 /LTB 4 scavenging lipocalins are closely related; that the biogenic amine binding site is probably ancestral; that tick lipocalins share a monophyletic origin with lipocalins from other metazoan and that apyrase activity probably evolved a single time in the ancestral tick lineage.…”
Section: Protein Family Specific Analysis: Characterizing Paralogsmentioning
confidence: 99%
“…A few studies have attempted to date the divergences of the protein families using molecular clock approaches (Louw et al 2013;Schwarz et al 2014b). However, due to low sequence similarity among family members, the trees obtained give contradictory results and general low branch support.…”
Section: Molecular Clock Dating and Salivary Protein Familiesmentioning
confidence: 99%
See 1 more Smart Citation